An Ectopic Breast Tissue Presenting with Fibroadenoma in Axilla. (27th March 2013) - Amaranathan, Anandhi; Balaguruswamy, Kanchana; Bhat, Ramachandra V.; Bora, Manash Kumar
Abstract : Introduction . The congenital anomalies of breast, especially the polymastia (supernumerary breast) and polythelia (supernumerary nipple), always do not fail to amuse the clinicians because of their varied presentations, associated renal anomalies, and pathologies arising from them. The axillary polymastia is a variant of ectopic breast tissue (EBT). Ectopic breast tissue can undergo the same physiological and pathological processes as the normally located breast. The incidence of fibroadenoma developing in ectopic breast is reported as a rare entity, the most common being the carcinoma. Case Presentation . A 31-year-old Dravidian female presented with a lump of 4 cm in the right axilla for the past year which gradually increased in size, giving discomfort. Our initial differential diagnosis was fibroadenoma, lipoma, and lymphadenopathy. Further investigation and histopathological report of excision biopsy confirmed it as a fibroadenoma on ectopic breast tissue in the axilla. Patient has no associated urological or cardiac anomaly. Conclusion . This case has been reported for its rarity and to reemphasise the importance of screening of EBT for any pathology during routine screening of breast.